2006
DOI: 10.1897/05-161r.1
|View full text |Cite
|
Sign up to set email alerts
|

A pollution‐monitoring pilot study involving contaminant and biomarker measurements in the Seine Estuary, France, using zebra mussels (Dreissena polymorpha)

Abstract: Abstract-Zebra mussel (Dreissena polymorpha) is an invasive species that has proliferated in European and North American rivers and lakes during the last century. In this study, D. polymorpha has been used to provide information on contamination levels and biological effects in the Seine Estuary (France). The bivalves accumulated polychlorinated biphenyls (PCBs) and polycyclic aromatic hydrocarbons (PAHs) to a high degree with values reaching 800 ng/g dry weight for PCBs (sum of 20 congeners), and 1,000 ng/g d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(38 citation statements)
references
References 34 publications
(37 reference statements)
1
37
0
Order By: Relevance
“…The Gironde Estuary The measured PAH concentrations were above 6000 ng g -1 dry wt of mussel tissues, and the PCB body burdens exceeded 3000 ng g -1 dry wt of mussel tissues (Table 1). The Seine Estuary is thus one of the most highly polluted sites in the world in regard to such compounds (Minier et al 2006).In the Mediterranean Sea, the mussels Mytilus galloprovincialis were mainly characterised by their relatively high levels of DDD, DDE and DDT accumulated in the tissues. The sum of the 3 compounds was 50 to 130 ng g -1 dry wt of mussel tissues for Sites 34 to 39.…”
mentioning
confidence: 99%
“…The Gironde Estuary The measured PAH concentrations were above 6000 ng g -1 dry wt of mussel tissues, and the PCB body burdens exceeded 3000 ng g -1 dry wt of mussel tissues (Table 1). The Seine Estuary is thus one of the most highly polluted sites in the world in regard to such compounds (Minier et al 2006).In the Mediterranean Sea, the mussels Mytilus galloprovincialis were mainly characterised by their relatively high levels of DDD, DDE and DDT accumulated in the tissues. The sum of the 3 compounds was 50 to 130 ng g -1 dry wt of mussel tissues for Sites 34 to 39.…”
mentioning
confidence: 99%
“…The range of contaminants accumulated in bivalves inform about the contamination status of the habitat where they live in an integrated way, while the cellular and molecular alterations eventually evolved in these bioindicator organisms inform about the relevance of that contamination. (Goldberg, 1975;de Lafontaine et al, 2000;Galloway et al, 2004;Smolders et al, 2004;Minier et al, 2006). It has been recognized, however, that a range of biomarkers routinely screened in cells, body fluids, tissues and organs of bioindicator organisms to interpret contamination impacts, primarily participate in the normal homeostasis of the organism, therefore, they are significantly influenced also by several environmental and biological factors.…”
Section: Introductionmentioning
confidence: 99%
“…In the pollution assessment of freshwater habitats the zebra mussel D. polymorpha proved to be an efficient sentinel organism because its ecophysiological features (abundance, wide distribution, high filtration rate, and ability to accumulate large amounts of anthropogenic contaminants) enabled reliable in situ habitat contamination evaluations (Kraak et al, 1991;de Kock and Bowmer, 1993;Roper et al, 1996). More recently, zebra mussels have been successfully used even in integrated biomarker assessment studies when bioaccumulated contaminant data revealed good correlation with alterations of several cellular-molecular biomarker endpoints in these mussels (de Lafontaine et al, 2000;Minier et al, 2006;Contardo-Jara et al, 2009;Faria et al, 2010). Focused research provided relevant information about the natural variability of biomarker responses in zebra mussels, particularly related to seasonality and reproduction status, that helped establish validated biomonitoring approaches for the assessment of the environmental significance of chemical contamination in freshwater habitats (Stoeckmann and Garton, 2002;Binelli et al, 2005;Guerlet et al, 2007;Faria et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…population growth and reproduction) to contaminant-induced effects is a huge challenge (Segner & Braunbeck 1998). In an attempt to elucidate causal relationships between effects at different levels of biological organization, the potential utility of biomarkers for monitoring both environmental quality and the health of organisms inhabiting the polluted ecosystems has received increasing attention during the last few years (Lopes et al 2001, de la Torre et al 2005, Mdegela et al 2006, Minier et al 2006. For the assessment of the consequences of waste water release and agricultural activities to fish populations in stream systems, a combination of structural indicators and biochemical biomarkers has been recommended (Adams et al 1989, 2000, Braunbeck & Völkl 1991, 1993, Oulmi et al 1995, Zahn et al 1995, Segner & Braunbeck 1998, Hinton et al 2001, Castano et al 2003.…”
Section: Introductionmentioning
confidence: 99%